Using community conversations on animal health as a Gender Transformative Approach - CGIAR Research Program on Livestock (2020)
The process has been implemented and the outcome documented, thus available for use. The next users are development agencies and government authorities looking for ways to progress towards gender and social equity goals, as well as public and private organisations working on animal health to adopt a gender equity lens.